2016
DOI: 10.1038/srep35754
|View full text |Cite
|
Sign up to set email alerts
|

Form, shape and function: segmented blood flow in the choriocapillaris

Abstract: The development of fluid transport systems was a key event in the evolution of animals and plants. While within vertebrates branched geometries predominate, the choriocapillaris, which is the microvascular bed that is responsible for the maintenance of the outer retina, has evolved a planar topology. Here we examine the flow and mass transfer properties associated with this unusual geometry. We show that as a result of the form of the choriocapillaris, the blood flow is decomposed into a tessellation of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 51 publications
3
89
1
Order By: Relevance
“…However, our data do not back a generalization for the whole choroid (Nickla & Wallman ; Zouache et al. ). The different diurnal patterns of CCP and SLP compared to MAP, could be due to the size of the vessels in both layers, as they are much smaller than in HL (Esmaeelpour et al.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our data do not back a generalization for the whole choroid (Nickla & Wallman ; Zouache et al. ). The different diurnal patterns of CCP and SLP compared to MAP, could be due to the size of the vessels in both layers, as they are much smaller than in HL (Esmaeelpour et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Histologic publications suggested that this instrument cannot detect the specific morphology of the normal vascular network in the choriocapillaris layer within the macular area 7–9 . We thus evaluated the intensity of the decorrelation signals as the index of blood flow but not the vascular structure per se in the choriocapillaris layer.…”
Section: Methodsmentioning
confidence: 99%
“…Both of the long posterior ciliary arteries divide the developing immature choroid along the horizontal meridian, preventing the superior precapillary branches of the short posterior ciliary arteries from connecting with inferior branches across the horizontal meridian. Only at the level of the choroidal capillaries is there a segmental connection across the horizontal meridian [44]. This is in contrast to the rodent's eye, where the superior and inferior hemispheres of the choriocapillaris are clearly separated by the nasal and temporal long posterior ciliary arteries [45].…”
Section: The Impact Of the Choroidal Development On Defining The Horimentioning
confidence: 99%